Clinico-etiolological Study of Hoarseness in 100 Patients (Journal of Fatima Jinnah Medical University, 2018)
Objective: To evaluate the role of FLEXIBLE FIBER OPTIC NASOPHARYNGOSCOPE /LARYNGOSCOPE in diagnosis of etiology of hoarseness.Setting: ENT Unit-1 Mayo Hospital, King Edward Medical University (KEMU), and Lahore Period: From Sep 2012 to March 2013.Material and Methods: Patients were admitted through ENT outpatient department. The data was collected on the basis of history, physical examination, investigations, flexible fiber optic nasopharngoscopy /Laryngoscopy, findings, management and follow up through standard questionnaire.Background: Hoarseness is a common symptom among patients who present to tertiary care hospitals . Patients with hoarseness are often referred for nasolaryngoscopy for evaluation to exclude serious conditions as laryngeal cancer.Study Design: This study is a retrospective case series in which 100 outpatients who presented with hoarseness were reviewed. We examined patients through Flexible fiber optic nasopharyngoscope / Laryngoscope, evaluate demographics, procedure indications, findings, complications, and advise management.Conclusion: Flexible fiber optic nasopharngoscopy /Laryngosopy is safe, noninvasive and the best procedure for diagnosis of dysphonia. We performed 100 cases with excellent diagnostic accuracy without leading to any serious complication. Flexible fiber optic nasopharngoscopy /Laryngosopy should be adopted in all out patient departments of tertiary care hospitals for accurate diagnosis and proper management of patients presented with hoarseness.Hoarseness is significant presenting complaint of laryngeal disorders and should not be ignored if it lingers beyond 3 weeks, not does not respond to conventional treatment.
Keywords: Hoarseness, Larynx, Flexible fiber optic Nasopharyngoscope/Laryngoscope